Gas-phase structures reflect the pain-relief potency of enkephalin peptides. Issue 41 (3rd October 2019) - Pereverzev, Aleksandr Y.; Szabó, István; Kopysov, Vladimir N.; Rosta, Edina; Boyarkin, Oleg V.
Abstract : Gas-phase structures can be used for evaluating the binding efficiency of enkephalin drugs into the hydrophobic pockets of opioid receptors. Abstract : We use cold ion spectroscopy and quantum-chemical computations to solve the structures of opioid peptides enkephalins in the gas phase. The derived structural parameters clearly correlate with the known pharmacological efficiency of the studied drugs, suggesting that gas-phase methods, perhaps, can be used for predicting the relative potency of ligand drugs that target the hydrophobic pockets of receptors.